Perceptions and Adaptation Strategies to Changing Climate: Evidence from Farmers of Northern Dry Zone of Karnataka - Dupdal, Ravi; Patil, BL; Naik, Bhupendra Singh (Indian Journal of Extension Education, 2025)
This study elicits and understands farmers’ perceptions and indigenous adaptation strategies to mitigate climatic variability in northern dry zone of Karnataka. Pre-tested and structured interview schedule was used to collect data from the farmers using multi-stage random sampling technique. Statistical tool like Garret ranking technique was employed to identify and rank various adaptation strategies practiced by farmers towards changing climate. Results revealed that farmers experienced varying climatic condition in terms of decreasing and unpredictable rainfall, increase in temperature in recent years and frequent failure of monsoon. Climatic variability affected farming in terms of declining crop yields, frequent crop failure, sinking water level in bore wells and open wells and increased emergence of new pest and diseases. Farmers manifested resilience against changing climate by adopting combination of indigenous and modern scientific adaptation strategies such as crop diversification, mixed farming, water conservation structures, changing planting dates, seeking off-farm employment and adopting drought and heat-tolerant varieties. Main barriers to adaptation were lack of knowledge about climate change, lack of timely availability of weather information and farm inputs. To enhance access and timely dissemination ofÂ weather forecasts information, timely availability of farm inputs and crop insurance mechanisms will have the scope to enhance farmers’ resilience to changing climate and adaptation.